Histopathological evaluation in post-mortem renal biopsies of patients with COVID-19 and comorbidities: a case-control study - Mehanna, Samya Hamad; Arantes, Mayara Pezzini; Proença, Henrique Machado de Souza; Weissheimer, Rafael; Ioshii, Sérgio Ossamu; Pires, Micheli Ito Gimenes; Barretto, Julia Wolff; Castro, Eduardo Morais de; Moraes, Thyago Proença de; Noronha, Lucia de (São Paulo Medical Journal, 2026)
BACKGROUND: Acute kidney injury is one of the main systemic complications of severe coronavirus disease 2019 (COVID-19). OBJECTIVES: To examine histopathological changes in post-mortem kidney biopsies of patients who died as a result of the disease caused by SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2). DESIGN AND SETTING: A case-control study was conducted at a tertiary hospital located in Curitiba, Paraná, Brazil. METHODS: The study group, called “COVID,” consisted of kidney biopsy samples obtained from deceased patients with COVID-19, with a “Control” group included for comparison. Samples were selected based on sex, age, and comorbidities, with an emphasis on diabetes mellitus and systemic arterial hypertension (SAH). Morphological evaluation was performed by pathologists using preestablished criteria with glomerular, tubular, and vascular characteristics among the parameters. RESULTS: Tubular atrophy and interstitial fibrosis, markers of chronic kidney injury, were observed with equal frequency in both groups, probably because of the initial pairing of the samples. These findings are in line with what would be expected from chronic exposure to proteinuria. In relation to SAH, the main identification was interstitial vascular damage, particularly arteriolosclerosis/arteriosclerosis. Acute tubular injury was the most frequently observed feature in patients in the COVID group, which was probably related to ischemic damage. CONCLUSION: This study demonstrated that the main change identified in the renal parenchyma of patients with COVID-19 was acute tubular injury, which was expected considering the context of severe systemic ischemia to which these patients are subjected, with the other findings being the consequences of chronic damage.